Targeted Suppression of CEACAM6 via pHLIP-Delivered RNAs in Pancreatic Ductal Adenocarcinoma - Hongsik Kim; Chang-Gok Woo; Seung-Myoung Son; Yong-Pyo Lee; Hee-Kyung Kim; Yaewon Yang; Jihyun Kwon; Ki-Hyeong Lee; Ho-Chang Lee; Ok-Jun Lee; Hye-Sook Han (Medicina)
Background and Objectives: Carcinoembryonic antigen-related cell adhesion molecule 6 (CEACAM6) is involved in pancreatic cancer progression and is an attractive therapeutic target for pancreatic cancer. In this study, we evaluated the therapeutic efficacy of small-interfering RNA (siRNA) targeting CEACAM6 (siCEACAM6) and the CEACAM6-suppressive microRNA-29a (miR-29a) in a pancreatic ductal adenocarcinoma xenograft mouse model using pH-low insertion peptide (pHLIP) technology, which targets the acidic tumor microenvironment. Materials and Methods: The delivery vectors for siRNA and miRNA were constructed by conjugating the peptide nucleic acid forms of siCEACAM6 and miR-29a to a peptide with a pHLIP, enabling the transport of siRNA and miRNA across the plasma membrane. The tumor-suppressive effects of pHLIP-siCEACAM6 and pHLIP-miR-29a were assessed in vivo using a BALB/c xenograft mouse model with the injection of the CFPAC-1 human pancreatic ductal adenocarcinoma cell line. Results: The treatment of CFPAC-1 cells with pHLIP-siCEACAM6 and pHLIP-miR-29a under acidic pH conditions suppressed CEACAM6 expression and decreased cell viability. In a xenograft mouse model, the intravenous injection of pHLIP-siCEACAM6 and pHLIP-miR-29a suppressed tumor growth by up to 25.1% (p < 0.01) and 21.2% (p < 0.01), respectively, compared to the control mice treated with pHLIP-scr. Conclusions: Our results demonstrated the efficacy of the pHLIP-mediated delivery of siCEACAM6 and miR-29a as a promising therapeutic strategy in a pancreatic ductal adenocarcinoma xenograft mouse model. The pHLIP technology, which targets the acidic tumor microenvironment, represents an innovative approach to the delivery of small RNAs to pancreatic ductal adenocarcinoma cells, providing new potential strategies for pancreatic cancer treatment.